Racial Differences in Neighborhood Safety, Poverty, and Self-Rated Health - Tran, Thanh V; DeMarco, Rosanna; Mataoui, Fatma Zohra; Wang, Kaipeng (Advances in Social Sciences Research Journal, 2015)
Objectives. Guided by a sociological model of the effects of neighborhood segregation and a quality of health model that includes the relationship between structure, process, and outcomes applied to neighborhoods, this study examines the effect of perceived neighborhood safety and poverty on self-rated health status across Asian, Black, Latino, and White Americans. Methods. We conducted a secondary analyses using the 2009 and 2011 California Health Interview Survey. The sample is comprised of 83,507 respondents aged 18 to 85 including 9,127 Asians, 4,029 Blacks, 12, 206 Latinos, and 58, 145 Whites. We used logistic regression and tested the interaction effects between race, neighborhood safety and poverty level on self-rated health. Results. The results revealed that race and perceived neighborhood safety had a statistically significant interaction effect on self-rated health (F (7, 73) = 43.60, p = .001). Similarly, the interaction effect between race and poverty on self-rated health was also statistically significant (F (7, 73) = 127.29, p = .001). Conclusion. Perceived neighborhood safety and poverty exert negative effect on self-rated health and their effects varied among racial groups. Both variables are important for the understanding of health disparities among racial groups. Using the context of structure, process, and outcomes within neighborhoods, the sociologic model of residential segregation which ties SES, neighborhood safety, and physical activity across races as predictors of perception of poor health continues to prevail.